Classification of successional stages in atlantic forests: a methodological approach based on a fuzzy expert system - Mota, Mauricio Tavares da [UNESP]; Bressane, Adriano [UNESP]; Frutuoso Roveda, Jose Arnaldo [UNESP]; Monteiro Masalskiene Roveda, Sandra Regina [UNESP] (Centro Pesquisas Florestais, Ufsm, 2019)
A method based on fuzzy modeling was developed for the classification of the stages of a forest succession. The construction of the model considered the criteria established by CONAMA, which define secondary vegetation in the initial, middle, and advanced stages of regeneration of the Atlantic Forest, as guidelines for the management of native vegetation in the state of Sao Paulo. The proposed model was applied for classifying cases reported in the literature, where floristic and phytosociological analysis of the forest structure had been performed employing the judgment of experts. The fuzzy modeling approach provided good agreement with the conclusions of the experts, according to the Kappa index. In conclusion, fuzzy modeling is a promising technique for addressing subjectivity and uncertainty in the classification of successional stages in the Atlantic Forest.
Keywords: Ecological succession; Fuzzy logic; Atlantic Forest